Kedudukan Żawil Arḥȃm Pada Warisan dalam Perspektif Hukum Islam - Gustina Harahap (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to determine the heirs in the żawil arḥȃm group according to Islamic law. And to find out the position of żawil arḥȃm in inheritance from the perspective of Islamic law. This research was carried out using library research and paying attention to the field (Field Research). Literature study is a process of searching for various literature, the results of studies related to the research to be carried out. Literature study can be likened to a key that will open everything that can help solve research problems. The results of the research show that the heirs in the żawil arḥȃm group are (1) maternal grandfather, (2) every grandfather or grandmother who dies gets an inheritance, (3) grandchildren from the daughter's side, (4) daughters from the brother's side. son, (5) Sister's son, (6) Mother's brother's son, (7) Mother's uncle, (8) Uncle's daughter, (9) Father's aunt (father's sister), ( 10) Maternal uncles and aunts (mother's brothers and sisters). This is explained by Imam Nawawi in the book Raudhatut Thâlibîn, and Wahbah Zuhaili in the book al-Fiqhul Islam wa Adillatuhu. Meanwhile, according to the Malik and Syafi'i schools of thought, dzawil arham does not inherit. If someone dies without leaving dzawil furudh or ashabah, while he has żawil arḥȃm, then tirkah is given to Baitul mal. Because in the verses Mawaris only explains the ashabul furudh and ashabah parts. Allah does not mention the żawil arḥȃm part at all. Meanwhile, Abu Hanifah and Ahmad are of the opinion that żawil arḥȃm was given a will based on the word of Allah SWT, Surah Al-Ahzab verse 6. And the position of żawil arḥȃm in inheritance is as a non-permanent heir (outside of fardhu and ashobah experts), and as a place to resolve inheritance problems when there are no fardhu and ashobah experts. And those who do not make the dzawil arham an irregular heir, then the settlement is through radd to the żawil furudh which takes precedence over the inheritance of the żawil arḥȃm, but they inherit together with the person who does not get the radd, namely husband and wife.